Effect of moisture management practices and zinc fertilization on growth, productivity and economics of pearl millet (Pennisetum glaucum)under pearl millet-mustard (Brassica juncea) system - VIKRAMARJUN, MADAM; MEENA, SAMRATH LAL; SHIVAY, Y S; KUMAR, DINESH; MEENA, MAHESH CHAND; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2025)
Rainfed farming, crucial for India’s food security, is severely impacted by moisture stress and nutrient deficiencies, particularly in semi-arid regions. The present study was carried out during the rainy (kharif) seasons of 2020 and 2021 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the combined effects of moisture management practices and zinc fertilization on the productivity, quality, and economic yields of pearl millet (Pennisetum glaucum L.) within the pearl millet-mustard (Brassica Juncea L.) cropping system, a staple in India’s dryland agriculture. The experiment was laid out in a split-plot design (SPD) replicated thrice. The main plot treatments focused on moisture conservation methods, including no mulch, straw mulch at 3 t/ha, Pusa hydrogel at 2.5 kg/ha, and Pusa hydrogel at 5 kg/ha. The sub-plot treatments addressed zinc fertilization, comprising no zinc application, soil application of 25 kg ZnSO₄·7H₂O/ha, soil application of 12.5 kg ZnSO₄·7H₂O/ha combined with a foliar spray of 0.5% ZnSO₄·7H₂O at the maximum tillering stage, and foliar sprays of 0.5% ZnSO₄·7H₂O at both the maximum tillering and before flowering stages. Results revealed that the applying Pusa hydrogel at 5 kg/ha substantially enhanced yield attributes, with the highest ear head length (28.5–29.2 cm) and weight (18.6–19.0 g). The application of zinc, specifically incorporating 12.5 kg/ha of ZnSO₄·7H₂O to the soil along with a foliar spray at the maximum tillering stage, significantly boosted yield by improving water absorption and enhancing drought resilience. Grain yields were highest with applying Pusa hydrogel @5 kg/ha (2.17–2.23 t/ha), while zinc fertilization increased grain zinc concentration by 15% and protein content by 10.84%. Economic analysis showed that Pusa hydrogel @5 kg/ha accrued the highest net returns, while 2.5 kg/ha dosage offered a cost-effective alternative for budget-conscious farmers. Therefore, it is recommended to apply Pusa hydrogel @2.5 or 5 kg/ha, combined with 12.5 kg/ha of ZnSO₄·7H₂O as a soil treatment, followed by a 0.5% foliar spray at the maximum tillering stage, for pearl millet cultivation within the pearl millet–mustard cropping system in western India to enhance crop performance, optimize resource use, and improve the economic sustainability of the cropping system.